Relationship between Social Support and Mental Health of Novice Nurses during Coronavirus Epidemic - Mohammadi, Sara; Kamali, Nasrin; Jamshidbeigi , Yousof; Zakariaee , Seyed Salman; Rostami , Aghil; Kenarkoohi , Azra (Advances in Nursing & Midwifery, 2021)
Abstract Background: Coronavirus has created a confusing and stressful situation around the world. In these circumstances, health care workers are most prone to vulnerability. The goal of this study was to investigate the relationship between social support and mental health of novice nurses during the outbreak of COVID-19 to provide basic information for intervention measures. Study design: cross-sectional study Methods: This study was performed in spring of 2020 in hospital affiliated with Ilam University of Medical Sciences. Data were collected using general information questionnaire, General Health Questionnaire (GHQ) and Phillip’s Social Support Questionnaire and analyzed by SPSS software, as well as descriptive and inferential statistics. Results: The total score of GHQ and social support was 24.58±12.063 and 70.77±9.761, respectively. There was a statistically significant inverse relationship between social support and mental health of participants. Among the demographic variables, there was a significant correlation between work experience, hospital, direct contact with COVID-19 patients and the number of working days in coronavirus ward with mental health and social support. Conclusion: The findings of the present study add to our knowledge obtained from previous studies by discovering the impact of social support on mental health of health care providers with special attention to novice nurses at the forefront. Ongoing monitoring of psychological consequences associated with COVID-19 outbreak and social support of them require further attention.